Paradigm Shift: Will “Productivism” Replace the Washington Consensus? - S. A. Tolkachev (Мир новой экономики, 2024)
The article examines the reasons for the emergence and theoretical content of a new political-economic concept “productivism”, which claims to be doctrinal, replacing the neoliberalism and the “Washington Consensus”. The article explains how productivism differs from previous economic theories. It also highlights some internal contradictions within productivism and explains why some people criticize it. Despite the fact that some authors consider productivism as a “New Supply-Side Economics”, we propose to treat this concept not in the context of economic theories, as it does not have the relevant paradigmatic characteristics, but within the family of political-economic doctrines aimed at the direct justiﬁcation of economic policy. In this case, productivism joins the American collection of “national developmentalism” doctrines, which has a long history and acute demand in the present period.